Síntomas al final de la vida - Murillo, Maite; Valentín, Vicente; Valentín, María (Psicooncología, 2004)
Cancer patients often die with serious unrelieved symptoms causing a distressing death for them and needless added suffering for their families. Many physicians have not trained to care for the dying patient. This work reviews the common symptoms in the final phase and describes the methods to control them and support the patient and family through this difficult time. These symptoms are so characteristic of the dying process that all the physicians should recognize them, be skilled in providing appropriate care, and prepare for problems that may arise.